Changes in various branches of the Brewer–Dobson circulation from an ensemble of chemistry climate models. Issue 1 (16th January 2013) - Lin, P.; Fu, Q.
Abstract : [1] We analyzed the changes of simulated Brewer–Dobson circulation (BDC) for 1960–2099 from 12 chemistry climate models participating the Chemistry‐Climate Model Validation activity phase 2 (CCMVal‐2). We decomposed the BDC into transition, shallow, and deep branches with vertical extent of 100–70, 70–30, and above 30 hPa, respectively. Models consistently simulate the acceleration in all three BDC branches over 140 years, but the acceleration rate of the deep branches is much smaller. The acceleration rate of the transition and shallow branches in general shows weak seasonal or hemispheric dependence and increases with time, consistent with the continuous and homogeneous increase of greenhouse gas concentrations. The trend magnitudes of shallow and transition branches differ from model to model, which are found to be associated with the simulated changes in subtropical jets and tropical upper tropospheric temperature. The acceleration of the deep branch is also a response to the increase of greenhouse gas concentrations but is modulated by the changes in ozone concentrations. The effect of ozone changes is particularly prominent in the southern deep branch during austral summer: almost all models simulated strong significant acceleration during the ozone depletion era, weak deceleration during the ozone recovery era, and near‐zero trends during the stable ozone era. However, the ozone effect is less evident in other seasons and in other branches.